2011
DOI: 10.26719/2011.17.8.663
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prophylactic antibiotic administration at the surgical ward of a major referral hospital, Islamic Republic of Iran

Abstract: We evaluated the appropriateness of antibiotic prophylaxis administered before surgery at a major referral hospital in Shiraz, against the American Society of Hospital Pharmacists (ASHP) guidelines. Data on surgical procedure, choice of antibiotic and administration were gathered for all surgeries performed on hospitalized patients during 15 days in March 2010. Of 155 patients included in the analysis, 98% received prophylactic antibiotic before surgery; according to ASHP guidelines, prophylaxis was needed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
37
5
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 27 publications
16
37
5
2
Order By: Relevance
“…Regarding the choice of antibiotics and sensitivity patterns of bacteria in local hospital, we found that only 6.1% of the antibiotic prophylaxis prescription was in accordance with the guidelines for prophylactic antibiotics. This result was comparable with the other study conducted in Iran that the appropriateness of choosing antibiotic prophylaxis for general surgery was about 7.5% [6] . Another previous study reported that the appropriateness of the selection of antibiotic prophylaxis in 3 hospitals (a government hospital, a medical college teaching hospital, and a corporate hospital) in Mangalore, India were 14.1%, 23.3% and 32.9% respectively [24] .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Regarding the choice of antibiotics and sensitivity patterns of bacteria in local hospital, we found that only 6.1% of the antibiotic prophylaxis prescription was in accordance with the guidelines for prophylactic antibiotics. This result was comparable with the other study conducted in Iran that the appropriateness of choosing antibiotic prophylaxis for general surgery was about 7.5% [6] . Another previous study reported that the appropriateness of the selection of antibiotic prophylaxis in 3 hospitals (a government hospital, a medical college teaching hospital, and a corporate hospital) in Mangalore, India were 14.1%, 23.3% and 32.9% respectively [24] .…”
Section: Discussionsupporting
confidence: 82%
“…Appropriate prophylactic antibiotics administration before surgery can reduce the incidence of SSI. However, inappropriateness of antibiotic prophylaxis administration is still commonly found in various surgical procedures, including orthopedic surgery [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in Asian countries have generally reported higher prevalence of inappropriate antibiotic use for prophylaxis (48-100%) when compared to developed countries (23.4%-55.2%) [15,16,17,18,19]. Inappropriate timing of antibiotic administration (36.4%) and inappropriate duration (34.5%) were found to be the main reasons for inappropriate prophylactic antibiotic which was also similar to previous studies [17,18,20].…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, studies from different countries have found that SAP was used excessively and inappropriately [8][9][10][11][12][13][14][15][16][17][18][19]. A wide variation of overall compliance was seen that range from 0 to 71.9% in various surgical procedures, majority of these studies revealed that noncompliance were in terms of selection, timing of administration and prolonged duration of SAP; indication and dose of SAP were more satisfactory compliant than other parameters [20].…”
Section: Introductionmentioning
confidence: 99%